Tests and analysis of RC building, with or without masonry infills, for instant column loss. (15th August 2019) - Stathas, Nikos; Karakasis, Ioannis; Strepelias, Elias; Palios, Xenfon; Bousias, Stathis; Fardis, Michael N.
Abstract: Abrupt loss of a ground story column was experimentally simulated on a 0.8:1-scaled model of a 2 × 3 bay, two-story concrete building with masonry infills along the perimeter of the second story. Three cases were investigated in the infilled building: loss of a column at a corner of the building, inside the plan area or at the perimeter; loss of the perimeter column was also studied with the infills removed and the weight on the model structure increased, to simulate a third story. In general, there was almost no visible damage after each test, neither in the concrete structure nor in the infills. Residual diagonal cracks were visible at the bottom face of slabs, starting from the removed interior column, and especially from the removed exterior column in the repeat test without infills; after the additional load on the floors had been removed, these cracks were not visible anymore. The excellent performance even without the infills is due to the continuity of the bottom bars of beams through the beam/column joints and to the placement of two-way top and bottom reinforcement throughout the slabs, continuous across the supports on beams. During the quasi-stationary free vibration stage that followed column removal, the accelerations measured on the slabs adjacent to the column being removed exceeded only marginally the acceleration of gravity upwards and downwards. This confirms that it is good practice to place two-way top reinforcement in slabs, as well as to use a magnification factor of 2 on the gravity loads of these slabs in pushdown analyses performed to investigate loss of column incidents. Numerical simulation of the tests was successful as far as the prediction of the residual deflections and the decay of vertical vibrations are concerned, but could not capture the high frequency features of the transient vibration.